When and Why a Squeakier Wheel Gets More Grease: The Influence of Cultural Values and Anger Intensity on Customer Compensation. (August 2019) - Glikson, Ella; Rees, Laura; Wirtz, Jochen; Kopelman, Shirli; Rafaeli, Anat
When customers express anger, do they gain greater returns, as suggested by the proverb "the squeaky wheel gets the grease"? If so, does the intensity of the squeak matter? In four studies, we explore employee compensation responses to customers who express relatively high- versus low-intensity anger in service-failure settings. The studies demonstrate that the cultural value of power distance (PD) moderates the relationship between emotional intensity and customer compensation: High-PD service employees offer less compensation to customers expressing higher intensity anger, and low-PD service employees offer more to customers expressing higher intensity anger. For high-PD service employees, this relationship between emotional intensity and compensation is mediated by the perceived appropriateness of the anger expression; for low-PD employees, it is mediated by perceived threat. However, when perceptions of threat are mitigated, low-PD service employees offer higher compensation to lower intensity anger, and this effect is mediated by perceptions of appropriateness. This research is the first to examine the effect of anger intensity in service-failure settings. For managers, the findings illuminate the importance of adopting a cultural lens when designing emotion management training programs and when setting practices for compensating angry customers.